ANALISIS YURIDIS TERHADAP PROSES LELANG JAMINAN GADAI DI PT.PEGADAIAN (PERSERO) UPC SUNGAI RAYA DALAM KOTA PONTIANAK - NIM. A1011211043, REVA DWI UTAMI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This study aims to analyze the auction process of pawned collateral at PT. Pegadaian (Persero) UPC Sungai Raya Dalam, Pontianak City, and to assess its compliance with the prevailing legal provisions, particularly in terms of transparency and public access to information. The background of the research is based on the importance of legal protection for customers and the need to evaluate auction procedures as a form of execution of rights over collateral assets. This research employs a normative and empirical juridical approach. The normative approach involves the examination of regulations related to the auction of pawned collateral, while the empirical approach is carried out through interviews with representatives of PT. Pegadaian (Persero) UPC Sungai Raya Dalam and members of the community. The study is descriptive-analytical in nature, using primary data obtained from interviews and secondary data from legal literature and relevant documents. Data collection techniques include literature study, interviews, and documentation, which are then analyzed qualitatively to assess the conformity of auction practices with legal norms and principles of transparency. The research findings indicate that, in general, the auction process of pledged collateral by PT. Pegadaian has complied with the applicable legal provisions, including the Civil Code (KUHPer), OJK Regulation Number 31/POJK.05/2016, Ministry of Finance Regulation Number 122/PMK.06/2023, and SOE Ministerial Regulation PER-2/MBU/03/2023. The stages of the auction process include the identification of pledged items, internal notification, valuation and appraisal, auction announcement, auction implementation, and recording of auction results. Although the procedures are generally in accordance with regulations, discrepancies were found in practice